Through a glass darkly - Kutsch, Elmar (Institute of Risk Management, 2023)
All over the world, companies and governments spend billions of dollars on what is euphemistically called risk management – gathering information about the future state and effect of their environment. Risk management is big business and becoming ever larger despite the worldwide downturn. For example, despite recent cost cutting and staff reductions, banks and broker dealers plan to increase their spending by $100 billion a year implementing risk governance frameworks by 2025. Risk management has been at the heart of organisations and standards in programmes that are promoted globally to increase the chance of success.